La consolidación de la élite intelectual en México (1867-1910) - Solórzano Ramírez, José Manuel (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
This research focuses on an effort from some aspects of history, to analyze the role of intellectuals linked to the Escuela Nacional de Ingenieros. A group formed based on informal relationships -kinship, clientelism, master-disciple relationship, friendship, etc.– which molded a well-defined social group. Social relations shows networks of intellectuals and power that can be formed into a formal institution. In the same way, it is a concern to show social actors in their own historical context, giving an interesting picture of his worldview, that is, as I thought concepts such as culture, society, citizen, literacy, education, civilization, etc. The research center is based on social relations that formed as a group of intellectuals associated with the School of Engineering. But at the same time, we express the importance of historical processes represented as the Enlightenment and modernization within the intellectual discourse, as well as the way in which influenced the construction of the modern nation-state in Mexico from 1867 to 1910. We show tangentially, as otherness was constructed, based on the intellectual discourse and in political hand, as influenced the process of nation building, civilization, barbarism, the modern and the traditional. Keywords: intellectual, social networks, critical discourse analysis, worldview, illustration, modernization, nation-state, modern, traditional, otherness.

Esta investigación se centra en realizar un esfuerzo, desde algunas vertientes de la historia, por analizar el papel de algunos intelectuales vinculados con la Escuela Nacional de Ingenieros. Un grupo formado con base en relaciones informales – parentesco, paisanaje, clientelismo, relación maestro discípulo, amistad, etc. –que moldearon un grupo social bien definido: las relaciones sociales muestran las redes de intelectuales y de poder que se pueden formar en una institución formal. De la misma manera, es una preocupación por mostrar a los actores sociales dentro de su propio contexto histórico, otorgando una imagen interesante de su visión de mundo, es decir, como pensaba conceptos como cultura, sociedad, ciudadano, instrucción, educación, civilización, etc. El centro de la investigación está fundamentado en las relaciones sociales que formaron como grupo a los intelectuales vinculados con la Escuela de Ingenieros. Pero al mismo tiempo, manifestamos la importancia que representaron procesos históricos como la Ilustración y la modernización dentro del discurso intelectual, así́ como la forma en como influyó en la construcción del Estado-Nación moderno en México de 1867 a 1910. Mostramos de manera tangencial, como se construyó la alteridad, en base al discurso intelectual y, en parte político, y como influyó en el proceso de construcción de la nación, la civilización, la barbarie, lo moderno y lo tradicional.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2016-1186; Opción en historia regional continental; Intelectuales; Redes sociales; Análisis críticos del discurso; Ilustración; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/292